1999
DOI: 10.1161/01.cir.99.22.2861
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Heparin Impairs Nitric Oxide Pathway and Vasomotion in Rats

Abstract: Background-Platelet-activating effects have been reported with high-dose heparin in acute thrombotic disorders. Recent studies have shown that increased platelet aggregation is due to reduced nitric oxide (NO) production in endothelial cells cultured in the presence of high-dose heparin. The aim of this study was to determine whether heparin can affect the NO pathway and the regulation of the vascular tone in vivo. Methods and Results-Anesthetized and mechanically ventilated Sprague-Dawley rats were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…4,6,34 In the present study, we hypothesized that competitive binding of heparin to glycocalyx-associated proteins would affect the mechanotransduction of shear stress to the endothelium. We found that a clinically relevant dose of heparin (Ϸ50 U/kg of body weight) was associated with an increased clearance of large dextrans from the systemic circulation and a reduction in the duration of arteriolar vasodilation during reactive hyperemia in the mouse cremaster muscle.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4,6,34 In the present study, we hypothesized that competitive binding of heparin to glycocalyx-associated proteins would affect the mechanotransduction of shear stress to the endothelium. We found that a clinically relevant dose of heparin (Ϸ50 U/kg of body weight) was associated with an increased clearance of large dextrans from the systemic circulation and a reduction in the duration of arteriolar vasodilation during reactive hyperemia in the mouse cremaster muscle.…”
Section: Discussionmentioning
confidence: 98%
“…2 In addition, there is evidence that heparin can induce antibodyindependent platelet activation, and this effect has been associated with an impaired endothelial NO production 3 and NO-dependent vascular reactivity. 4 On the other hand, increases in endothelial NO production and associated arteriolar vasodilation by heparin have been reported as well. 5,6 Heparin exerts its anticoagulation effect primarily by catalyzing the inhibition of thrombin by the serine protease inhibitor antithrombin III, apparently as a result of a conformational change within antithrombin III.…”
mentioning
confidence: 95%
“…Heparin administration has been reported to augment (Kouretas et al, 1998) or impair (Bachetti et al, 1999) endothelial function. However, according to our procedure, in which we tried to minimize the dose of heparin given to the rat, we found neither the activation-flow coupling response nor the clip responses changed during experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although eNOS was increased, the expression of eNOS mRNA was not, suggesting modulation occurs at the level of translation rather than transcription (17). However, these findings are contradicted by Bachettie et al (1), who reported a decrease in aortic eNOS protein expression and impairment of NO-dependent vascular reactivity after heparin infusion in rats. It is unlikely that inducible NOS plays a significant role because our laboratory's previous studies have indicated that it is minimally present compared with eNOS in normoxic or hypoxic rats (5).…”
mentioning
confidence: 87%